2014
DOI: 10.1002/j.1556-6676.2014.00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Causal Impacts of School Counselors With Regression Discontinuity Designs

Abstract: This article presents a causal regression discontinuity framework for quantifying the impact of high school counselors on students’ education outcomes. To demonstrate this method, the authors used data from the National Center for Education Statistics’ Schools and Staffing Survey (SASS). Using high school counselor staffing counts and 4‐year college‐going rates collected through the SASS, the authors found that an additional high school counselor is predicted to induce a 10 percentage point increase in 4‐year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…School counselors have the potential to increase access to postsecondary opportunities by providing career and college readiness counseling (Bryan, Moore‐Thomas, Day‐Vines, & Holcomb‐McCoy, 2011). The effect that school counselors have on students’ career and college readiness on college‐eligibility information, application completion, and enrollment plans is evident throughout the related research (Hurwitz & Howell, 2014; Lapan, Whitcomb, & Aleman, 2012; Robinson & Roksa, 2016). School counselors are expected to prepare students for postsecondary pathways from as early as kindergarten through 12th grade.…”
mentioning
confidence: 98%
“…School counselors have the potential to increase access to postsecondary opportunities by providing career and college readiness counseling (Bryan, Moore‐Thomas, Day‐Vines, & Holcomb‐McCoy, 2011). The effect that school counselors have on students’ career and college readiness on college‐eligibility information, application completion, and enrollment plans is evident throughout the related research (Hurwitz & Howell, 2014; Lapan, Whitcomb, & Aleman, 2012; Robinson & Roksa, 2016). School counselors are expected to prepare students for postsecondary pathways from as early as kindergarten through 12th grade.…”
mentioning
confidence: 98%
“…Several studies support the effect that school counselors can have on the college readiness of students by increasing their postsecondary knowledge, and assisting with their college applications and enrollment plans. Hurwitz and Howell (2014) found that the addition of just one high school counselor may result in a 10% increase in the college enrollment of students from that school. This may be because additional school counselors can increase the number of applications students make to 4-year colleges (Robinson & Roksa, 2016) and can provide extended benefits that can positively impact students' college planning and preparation (Lapan, Whitcomb, & Aleman, 2012).…”
mentioning
confidence: 99%
“…We might not be surprised that the point estimate is small given the intervention adds only one college adviser in an entire high school. One noisy estimate of the effect of an additional high school counselor on college enrollment suggests an additional counselor might increase college going by 10 percentage points (Hurwitz & Howell, ), but those results appear to be driven by increasing from one to two counselors at very small schools. Schools in our sample are, on average, over four times as large likely resulting in a diluted effect.…”
Section: Resultsmentioning
confidence: 99%